Using Machine Learning Models for Inpatient Bed Demand Forecasting in the UAE Hospitals - Sheiko, Rahaf Abdulla (2024)
A Master of Science thesis in Engineering Systems Management by Rahaf Abdulla Sheiko entitled, “Using Machine Learning Models for Inpatient Bed Demand Forecasting in the UAE Hospitals”, submitted in July 2024. Thesis advisor is Dr. Rami Afif As’ad and thesis co-advisor is Dr. Hussam Alshraideh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).